MODEL OF INVESTMENT STRATEGIES IN CYBER SECURITY SYSTEMS OF TRANSPORT SITUATIONAL CENTERS - Akhmetov, B. B.; Lakhno, V. A.; Malyukov, V. P. (Radio Electronics, Computer Science, Control, 2018)
Actuality. The actual task of finding the optimal strategy for control the procedure of mutual financial investments to the situation center for cyber security on transport. The aim of the work – the development of a model for a decision support system on the continuous mutual investment in a cyber security situational center, which differs from the existing ones by solving a bilinear differential quality game with several terminal surfaces. Method. In order to achieve the goal there was used a discrete-approximation method for solving a bilinear differential quality game with dependent motions. Application of this method in the developed decision support system, unlike existing ones, gives concrete recommendations ft choosing control decisions in the investment process. Results – the proposed model gives concrete recommendations at choosing strategies in the investment process at the creation of a protected situational center. In the course of the computational experiment, there was considered a new class of bilinear differential games that allowed adequately to describe the process of investing in cyber security means of situational transport centers in Kazakhstan and Ukraine. Conclusions. For the first time, there was proposed a model describing the process of mutual investment based on the solution of bilinear equations and a differential quality game with several terminal surfaces. Considered the peculiarity of the differential game on the example of mutual investment in the means of cyber security of the situational transport center. In this case, the right-hand side of the system of differential equations is represented in the form of bilinear functions with arbitrary coefficients. The model allows to predict the results of investment and to find strategies for managing the investment process in the protection and cyber security systems of the situational transport center.